Posterior Nutcracker Phenomenon in a Patient with Left Atrial Isomerism - Tsvelodub, Stanislav; Putman, Léon M.; Gieselmann, Andrea; Sievers, Hans-Hinrich (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Background Nutcracker phenomenon (NCP) can occur due to various anatomical anomalies. Anterior and posterior NCP are defined in the literature. Posterior NCP combined with left atrial isomerism is a rare condition.Case description We present a rare case of an asymptomatic posterior NCP involving the azygos vein in a patient with a complex cardiovascular pathology with left atrial isomerism, left ventricular outflow tract obstruction, interrupted inferior vena cava, and azygos continuation.Conclusion Detection of the NCP especially involving such a rare anatomical anomaly as an azygos continuation has a crucial importance for diagnostic and surgical procedures.
Keywords: congenital heart disease; magnetic resonance imaging; pediatric; cardiovascular surgery